Dilemma of an island - Gunaratne, Merril (Colombo : Vijitha Yapa Publications, 2001)
Reminiscences of a former senior deputy inspector general of police, Sri Lanka.
Keywords: Sri Lanka -- Social conditions; Sri Lanka -- Ethnic relations